Sustaining International Partnerships: The European Master of Science Programme in Occupational Therapy, a Case Study. - Ilott, Irene; Kottorp, Anders; Cour, Karen; Nes, Fenna; Jonsson, Hans; Sadlo, Gaynor (Occupational Therapy International, 2013)
International partnerships are a mechanism for supporting the academic development of occupational therapy and promoting cultural competence. This case study describes the factors that have helped to sustain a post-qualifying programme implemented by five higher education institutions in Denmark, the Netherlands, Sweden, Switzerland and the UK since 1999. Data collection methods were documentary analysis and the reflections of a purposive sample of six key informants. Cohort and outcome data, from 193 students from 31 countries who enrolled between 1999 and 2011, are reported. Each cohort comprises students from an average of eight countries to optimize inter-cultural dialogue. Four factors support sustainability. These are 1) supportive professional European networks; 2) timeliness and alignment with European higher education policy; 3) partnership structures and processes that emphasize joint decision making and accountability; and 4) the stimulus and satisfaction associated with internationalization. The main limitations are considering the OT-EuroMaster as an intrinsic case study and using opportunistic data collection that undermines the rigor and transferability of the findings. Future opportunities include doctoral networks, transnational research and sharing our curricula design with other Regions to spread the collaborative, capacity building endeavours more widely. Copyright © 2013 John Wiley & Sons, Ltd.